On the geographical distribution of the Neotropical and Andean species of Schendylops (Chilopoda: Geophilornorpha: Schendylidae) - Morrone, Juan José (1999)
The geographical distribution of the 49 Neotropical and Andean species of Schendylops was analyzed. Themajority of the species are Neotropical, being endemic to the Caribbean (six species), Amazonian (10 species), Parana(11 species), and Chacoan (seven species) subregions. Seven species are distributed in the Andean region: in the Paramo-Punan (six species) and Patagonian (one species) subregions. No generalized track was obtained, but connections between different subregions were found, being coincident with previous studies that recognised the Neotropical and Andean components within South America.